Effect Work-Life Balance on Organizational Commitment: Is The Role of Organizational Citizenship Behavior? - Eriyanti, Hanum Febby; Noekent, Vitradesie (Universitas Negeri Semarang, 2021)
Balancing work and life stand as an on-going challenge in contemporary times. In organizational context, a high quality of work–life balance is crucial to continue attracting and retaining its employees. The purpose of this study was to determine the relationship between WLB and OCB through OC as a mediation. A survey was conducted using a set of established questionnaires on work–life balance, organizational citizenship behaviour and organizational commitment with employees of State Civil Apparatus who work in the Office of Education, Youth and Sports in Kudus Regency. The sampling technique in this study used a saturated sampling technique with a total of 86 employees. Methods of data analysis using descriptive statistical tests and software SmartPLS 3.0. The results showed that WLB had a positive and significant relationship on OC and OCB. OC is also shown to have a positive and significant relationship with OCB. In addition, OC was shown to be able to mediate the relationship between WLB and OCB. Theoretical suggestions for further research are to develop independent variables other than WLB and OCB and choose respondents from other sectors. The study has suggested implications for researchers and practitioners in the field of human resource management and experts in the area of organizational development.